2019
DOI: 10.1111/jon.12667
|View full text |Cite
|
Sign up to set email alerts
|

Flat‐Detector CT to Quantify Response to Intra‐Arterial Spasmolytic Therapy for Cerebral Vasospasm

Abstract: BACKGROUND AND PURPOSE Cerebral vasospasm in the setting of subarachnoid hemorrhage causes morbidity and mortality due to delayed cerebral ischemia and permanent neurological deficits. Vasospasm treatment includes intra‐arterial injection of a spasmolytic during cerebral angiography. To evaluate effectiveness, neurointerventionalists subjectively examine a posttreatment cerebral angiogram to determine change in vessel diameter or increase in microvascular perfusion. Flat‐detector computed tomography (FDCT) sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…A small prospective study of a cohort of six patients confirmed the applicability of FD CT PBV measurement in patients with post subarachnoid hemorrhage vasospasm treated with intra-arterial Verapamil injections [ 76 ]. They demonstrated significant increases of blood volumes in treated brain areas post intra-arterial treatment, signifying favorable treatment effect.…”
Section: Applications Of Fd Ct Pbvmentioning
confidence: 97%
“…A small prospective study of a cohort of six patients confirmed the applicability of FD CT PBV measurement in patients with post subarachnoid hemorrhage vasospasm treated with intra-arterial Verapamil injections [ 76 ]. They demonstrated significant increases of blood volumes in treated brain areas post intra-arterial treatment, signifying favorable treatment effect.…”
Section: Applications Of Fd Ct Pbvmentioning
confidence: 97%